Manage me a proposed project management application for senior visual communication students who freelance in digital design and illustration - Azarcon, Kyle V.; Dans, Sandra Michelle (Quezon City College of Fine Arts, University of the Philippines Diliman, 2024)
Senior visual communication students who freelance in digital design illustration in University of the Philippines Diliman often feel overwhelmed and pressured by the multiple tasks, and meeting deadlines for both school and freelancing work requires excellent organizational skills, and addressing these challenges requires careful planning.

The effective strategies these freelance students use to aid the current situation are setting goals and tracking tasks using either online tools such as Asana, Trello, Slack, Keep notes, Milanote, Notion, etc. and analog tools such as manual planning through listing tasks using notebook, calendar, or planner. Despite having these tools available, freelance students still procrastinate resulting in overwhelming and little no motivation. One of the skills this field requires is time management, with effective strategies such as setting goals, tracking progress of tasks, and organizing projects to perform greater productivity and creativity.

Manage me caters and identifies the needs of the senior visual communication students who freelance in digital design and illustration by offering a design solution: usability, encouraging engagement, and clear and innovative that promotes productivity and creativity. Manage me is a proposed project management mobile application to support the stakeholders by bringing the materials integrated to UP Mail and freelance projects with its resources into one place, addressing the research problem: how might we help senior visual communication students at University of the Philippines Diliman who freelance in digital and illustration work manage their priorities in studies while working on their freelance project.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 53-55
Keywords: Freelancing; Freelancers; Time management